P5 Implementation Strategy in Islamic Religious Education in Building Environmentally Friendly Student Character - Afiyah, Umu; Muhid, Muhid; Saefrudin, Saefrudin (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2025)
This study aims to analyze the role of the Pancasila Student Profile Strengthening Project (P5) in Islamic Religious Education (PAI) learning as an instrument for developing students’ environmentally oriented character at SMK Fathul Hidayah Pangean Lamongan. The research background is based on the low environmental awareness among students despite the fact that PAI subjects emphasize Islamic moral values. This study employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The results indicate that integrating P5 into PAI learning fosters students’ ecological awareness by internalizing the values of amanah (trust), khalifah (stewardship), and ihsan (excellence), implemented through project-based activities. These activities include waste management, tree planting, and environmental awareness campaigns that actively involve student participation. The application of this strategy has proven effective in developing caring and responsible attitudes toward the environment, although challenges remain, such as limited resources and teachers’ pedagogical competence in managing integrative learning. The study recommends enhancing teacher capacity through continuous training and developing more creative and integrative learning models between P5 and PAI to expand the positive impact on strengthening students’ character, particularly in the aspect of sustainable environmental awareness.